Case Report of Neurocardiogenic Vasovagal Shock: “A Medicolegal Mas- querade” (Indian Internet Journal of Forensic Medicine and Toxicology, 2025)
Autopsy plays a significant role in determining the cause of both natural andunnatural deaths. Identifying the cause of death becomes more challenging when itoccurs suddenly and rapidly, particularly in cases involving trauma, whether knownor unknown, or in a case of concealed underlying pathology. The role of cardiacinhibitory reflex as a potential cause of death remains debatable. This case reportdescribes a fatal incident of such nature. The reasons for such neurocardiogenicvasovagal shock can be attributed to sudden shock or strong emotions and injuryto specific areas such as the carotid sinus, various plexuses, testicles, and serousmembranes. Even minor trauma to these areas can lead to sudden death. This casereport describes a 43-year-old male who was assaulted by his neighbour as a resultof a long-standing feud and died almost immediately after minor trauma to the neckand chest.
Keywords: Autopsy; Neurocardiogenic Vasovagal Shock; Trauma; carotid sinus